The Coptic Theme in Egyptian novels The case of Bayt al-Qibṭiyya (“The house of the Copt woman”) by ʼAšraf al-‘Ašmāwī - Naglaa Waly (Kervan. International Journal of Afro-Asiatic Studies, 2021)
This article discusses Bayt al-Qibṭiyya (“The Hhouse of the Copt woman”), a novel by ʼAšraf al-ʻAšmāwī; published in 2019, the novel is a recent iteration of the Coptic theme in Egyptian fiction.